ZIF-8-loaded decellularized porcine annulus fibrosus bioadhesive enhances rotator cuff tendon-to-bone healing in a rat model - Xiping Jiang; Hui Xu; Xinyue Sun; Xuefan Yang; Yuxuan Xia; Wen Xue; Yaohua He; Yaohua He (Frontiers in Bioengineering and Biotechnology)
IntroductionThe high rate of retear following rotator cuff repair is largely attributed to the absence of a fibrocartilage layer and limited bone regeneration capacity. We aim to evaluate a bioadhesive derived from decellularized porcine annulus fibrosus extracellular matrix, loaded with zeolitic imidazolate framework-8 (ZIF-8), and to promote rotator cuff tendon–bone healing.MethodsThree adhesive formulations were developed: (1) silk fibroin/tannic acid (ST group), (2) ST combined with decellularized porcine annulus fibrosus extracellular matrix (ST/dECM group), and (3) ST/dECM supplemented with ZIF-8 (ST/dECM/ZIF-8 group). Optimal component ratios were determined using lap shear strength testing. The microstructure, Fourier transform infrared (FTIR) spectra, swelling behavior, and degradation properties of the materials were characterized. In vitro studies assessed the adhesives’ effects on cytotoxicity, proliferation, and the chondrogenic and osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (BMSCs). A rat rotator cuff repair model was used to evaluate in vivo anti-inflammatory effects, fibrocartilage and bone regeneration, and biomechanical performance.ResultsAll adhesive formulations exhibited comparable tissue adhesion strength and biocompatibility. Both the ST/dECM and ST/dECM/ZIF-8 groups enhanced BMSC chondrogenic differentiation compared to the ST group, with the ST/dECM/ZIF-8 group showing superior osteogenic induction. In vivo, the ST/dECM/ZIF-8 hydrogel effectively reduced interfacial inflammation and promoted fibrocartilage and bone regeneration. Biomechanical testing demonstrated significantly higher ultimate load, tensile stress, and stiffness in all adhesive-treated groups compared to untreated controls.ConclusionThe ST/dECM/ZIF-8 bioadhesive hydrogel promotes fibrocartilage and bone regeneration. These findings highlight its potential as a promising biomaterial-based strategy to enhance tendon-to-bone interface healing following rotator cuff repair.